Addressing HIV/AIDS in East Asia and the Pacific. (Health, nutrition, and population series., 2004)
"This volume shows how the World Bank, working together with governments, civil society, and other development partners, can play a critical role in focusing efforts on the risk factors associated with concentrated HIV/AIDS epidemics. This book charts the nature of the epidemic in the region, surveys some of the successful practices currently being pioneered, and offers suggestions as to how the distinct characteristics of the HIV/AIDS epidemic faced in each country can be addressed by effective and comprehensive responses at both the country and regional levels. Addressing HIV/AIDS in East Asia and the Pacific will be of interest to policymakers, specialists, and all individuals and institutions that share the World Bank's goal of preventing the East Asia and Pacific region from becoming the future epicenter of HIV/AIDS."--Jacket